The Image of Great Britain in the social and political discourse of Spanish America on the Eve of the Wars of Independence - Polić-Bobić, Mirjana (Array, 1998)
The text deals with the image-forming of other cultures and societies in Spanish America on the eve of the wars of independence. In that context, it stresses the leading position of the image of Great Britain as just, pogressive and desirable society and points out the texts, written mainly by the ideologists of the independence, where that image further develops. The parallel process of demonization of Spain and Spanish colonial politics in Europe and America, as well as the renewal of the black legend i brought into close connection with it.